The Effects of Drying Methods, Packaging Atmosphere and Storage Time on Dried Pomegranate Aril Quality - Muharrem Gölükcü (Journal of Agricultural Sciences)
The aim of this work was to evaluate the effects of drying methods, packaging atmosphere, and storage time in preserving the quality of dried pomegranate aril on total phenolic matter, total anthocyanin, antioxidant activity, and CIE L, a*, b*, C, h colour values. The highest contents of phenolic matter (5580 mg kg-1), anthocyanin (679.76 mg kg-1), antioxidant capacity (IC50, 26.16 mg g-1) and CIE a* colour value (10.73) were observed in freeze dried sample, followed by vacuum, convective, and sun dried samples in descending order. Phenolic matter, anthocyanin, antioxidant capacity (1/IC50) and CIE a*, b*, C colour values of the samples packed under nitrogen gas were higher than those packed under air atmosphere. Significant changes in the quality parameters of the product were examined during storage, and the highest loss was determined in anthocyanin content among analyzed quality parameters. The result of present study indicated that freeze drying was the best method for dried pomegranate aril production